CONTROLLING ANDROID-BASED ELECTRICAL EQUIPMENT (LIGHTS) USING A SMARTPHONE WIFI CONNECTION - Payung Langi, Jeffrey (INFOKUM, 2022)
Control of electrical equipment (lights) is mostly controlled manually Even though with current technological advances, it can be optimized so that when the user wants to turn on or turn off the light, he doesn't have to press the switch. A touch of more sophisticated technology is needed to overcome problems like this. Therefore, the connection between the ZTE 609 modem, the Sonoff WiFi module and the smartphone based on the Android application in the electrical equipment control system will be a solution to control and monitor electrical equipment (lights) in real time using a WiFi connection.